2005
DOI: 10.1111/j.1744-7348.2005.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of spoilage storage rots of white yam (Dioscorea rotundata Poir.)

Abstract: Severity of storage rots in different sections of white yam tubers (Dioscorea rotundata Poir.) was investigated. Yam samples with rots were collected from a yam barn and from selected markets in Accra, Ghana, to identify the most predominant pathogens associated with the rots. Nine fungal spoilage microorganisms, including Aspergillus flavus, Aspergillus niger, Botryodiplodia theobromae, Fusarium culmorum, Fusarium oxysporium, Fusarium sp., Penicillium brevi-compactum, Penicillium sp. and Rhizopus stolonifer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…This fungus is also reported to infect severely roots such as white yam (Dioscorea rotundata) in Ghana. In this study, out of the 10 microorganisms isolated from this tuber, R. stolonifer incidence was in a range of 20 to 55% depending on the market sampled (Aboagye-Nuamah et al, 2005). In other studies, Bautista-Baños et al (2008) reported that in tomatoes collected from 15 different local markets in the state of Morelos, Mexico, R. stolonifer was the most predominant fungus, isolated from almost 50% of the samples.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This fungus is also reported to infect severely roots such as white yam (Dioscorea rotundata) in Ghana. In this study, out of the 10 microorganisms isolated from this tuber, R. stolonifer incidence was in a range of 20 to 55% depending on the market sampled (Aboagye-Nuamah et al, 2005). In other studies, Bautista-Baños et al (2008) reported that in tomatoes collected from 15 different local markets in the state of Morelos, Mexico, R. stolonifer was the most predominant fungus, isolated from almost 50% of the samples.…”
mentioning
confidence: 70%
“…Water-soaked appearance, tissue softening and collapse Zitter et al, 1998 Chilli Fruit - Meon and Nik, 1988;Adikaram, 1993;Thind and Jhooty, 1985 Date Fruit - Al-Hindi et al, 2011;Durian Fruit - Adikaram, 1993;Teng-fei et al, 2009 Eggplant Fruit Water-soaked areas, brownish liquid, characteristic odor Zacharia and Philip, 2010 Grapes Fruit Soft pedicels, watery rots and complete decay Latorre et al, 2002 Guava Fruit Oily lesion and water soaked, quick lesion expansion Ooka, 1980 Jackfruit Flowers, fruit Watery brown spots, black rotten, shrunken and mummification Nelson, 2005;Hossain et al, 2010 Mango Fruit Water-soaked lesion and rapid decay Teng-fei et al, 2009;Rathod, 2010 Papaya Fruit Soft and watery surface, intact fruit interior Alvarez and Nishijima, 1987;Adikaram, 1993;Akinmusire, 2011;Singh et al, 2012 Peas and beans Fruit Decay tissue typically watery, fluid leakage Snowdon, 1991 Snowdon, 1991;Edmunds and Holmes, 2009 Taros and tannias Roots Broken skin, soft pale tissue, cheese watery consistency yeasty odor Snowdon, 1991 Tomato Fruit Watery soaked Kwon et al, 2001;Mahovic et al, 2006;Akinmusire, 2011 White yam tubers Roots Rapid collapse of cell walls turning brown, soft and wet Aboagye-Nuamah et al, 2005;Nahunnaro, 2008 -; Not reported. *Symptoms for all the above-mentioned fruits and vegetables also include host covered by coarse, gray and hairy white mycelia that usually form a mass of visible black sporangia at their tips.…”
Section: Fruitmentioning
confidence: 97%
“…Seven of the identified fungi in this work have been isolated and identified to be rot-causing organisms in other research works done (Okigbo and Ikediugwu, 2002;Aboagye-Nuamah et al, 2005). L. theobromae and Penicillium oxalicum were reported to cause dry rot of yam (IITA, 1993), whilst Rhizopus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Lenticel spot can also be caused by one or more species of Pectobacterium. However, other bacteria such as species of Bacillus, Clostridium and Pseudomonas are also suspected to cause symptoms of lenticel spot (Aboagye-Nuamah, et al, 2005 andAidoo, 2007). Wet fields and warm temperatures before harvest, plus a film of moisture on the tuber surface either in storage or transit, greatly favor development of both diseases (Ravi and Aked, 1996).…”
Section: Effect On Rate Of Sprouting and Development Of Soft Spotsmentioning
confidence: 99%